IKr Impact on Repolarization and Its Variability Assessed by Dynamic Clamp. (October 2015) - Altomare, Claudia; Bartolucci, Chiara; Sala, Luca; Bernardi, Joyce; Mostacciuolo, Gaspare; Rocchetti, Marcella; Severi, Stefano; Zaza, Antonio
Abstract : Background—: Repolarization and its stability are exquisitely sensitive to I Kr features. Information on the relative importance of specific I Kr abnormalities is missing and would assist in the evaluation of arrhythmogenic risk. Methods and Results—: In single guinea-pig myocytes, endogenous I Kr was replaced by modeled I Kr (m I Kr ) by dynamic clamp (DC) at a cycle length of 1 s. m I Kr parameters were systematically modified, and the resulting changes in action potential duration (APD) and its short term variability (SD1) were measured. We observed that (1) I Kr blockade increased SD1 more than expected by its dependency on APD; (2) m I Kr completely reversed APD and SD1 changes caused by I Kr blockade; (3) repolarization was most sensitive to inactivation shifts, which affected APD and SD1 concordantly; (4) activation shifts of the same magnitude had marginal impact on APD, but only when reducing m I Kr, they significantly increased SD1; (5) changes in maximal conductance resulted in a pattern similar to that of activation shifts. Conclusions—: The largest effect on repolarization and its stability are expected from changes in I Kr inactivation. APD is less sensitive to changes in other I Kr gating parameters, which are better revealed by SD1 changes. SD1 may be more sensitive than APD in detecting I Kr -dependent repolarization abnormalities. Abstract : Supplemental Digital Content is available in the text.